(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
In this work I critically reflect, on how the protagonists reconcile the practices of ancestral medicine and western medicine in the dynamics of public service, in the ambit of the Health Center of the Municipality of Nagarote in León - Nicaragua. To reflect, I use to the categories of analysis supported by the work on community dynamics of the teacher and researcher Luis Felipe Ulloa, in particular the categories: PRACTICE, DYNAMICS, AMBIT AND PROTAGONISTS. In relation to the theoretical and methodological, I am located from constructivism and phenomenology as a theoretical route in this anthropological work, based on the perspective on case studies by Gilberto Giménez and Catherine Heau Lambert. I would like to point out that the first dives in the context gave me quick conclusions about a promising conciliation between the practices of medicine, both ancestral and western, within the dynamics of public service intervention, dymanics healthy living and dymanics political legal life; However, the subsequent incursions, dialogues, gatherings, showed me values, beliefs and conflicting ancestral practices, with the potential for the appearance of conflicts that are now it under of de table, and that are cultural, while opening the reflection on the present and emerging leadership as a resistance force or transformer of a more beautiful reality.